Genetic polymorphisms at the leptin receptor gene in three beef cattle breeds - Almeida, Sabrina Esteves Matos (2008)
The genetic diversity of a single nucleotide polymorphism (SNP) at the exon 20 (T945M) of the leptin receptor gene (LEPR) and of three short tandem repeats (STRs BM7225, BMS694, and BMS2145) linked to LEPR was investigated in three beef cattle herds (Brangus Ibagé, Charolais, and Aberdeen Angus). A cheap and effective new method to analyze the T945M polymorphism in cattle populations was developed and the possible role of these polymorphisms in reproduction and weight gain of postpartum cows was evaluated. High levels of genetic diversity were observed with the average heterozygosity of STRs ranging from 0.71 to 0.81. No significant association was detected between LEPR markers and reproductive parameters or daily weight gain. These negative results suggest that the LEPR gene polymorphisms, at least those herein described, do not influence postpartum cows production.